Which anthropometric equation to predict body fat percentage is more strongly associated with maximum oxygen uptake in adolescents? A cross-sectional study - Gonçalves, Eliane Cristina de Andrade; Nardo Júnior, Nelson; Ribas, Michele Caroline de Souza; Silva, Diego Augusto Santos (São Paulo Medical Journal, 2023)
BACKGROUND: Identifying the relationship between maximum consumption of oxygen and body fat percentage is important due to increased cardiovascular risk factors. OBJECTIVE: This study aimed to verify the association between body fat percentage determined by three predictive equations using anthropometric measures (Lohman, Boileau, and Slaughter) and maximum oxygen uptake (VO2max). We also aimed to estimate the capacity of these equations for explaining VO2max variations in adolescents according to sex. DESIGN AND SETTING: This was a cross-sectional study conducted in high schools in São José, Southern Brazil. METHODS: This study included 879 adolescents (14–19 years) from Southern Brazil. Aerobic fitness was assessed using the modified Canadian Aerobic Fitness Test. The independent variable was body fat percentage predicted by the Lohman, Boileau, and Slaughter equations. Analyses adjusted for sociodemographic variables, physical activity level, and sexual maturation were performed with P value < 0.05. RESULTS: All anthropometric prediction equations used to estimate body fat percentage explained VO2max variations in adolescents. In male adolescents, both regression models based on the Boileau et al.12 and Lohman10 equations revealed higher explanatory power for VO2max (20%) compared with that based on the Slaughter et al.13 equation (19%). In female adolescents, the model based on the anthropometric equation of Slaughter et al.13 showed the greatest explanatory power for VO2max (18%). CONCLUSION: The inverse relationship between VO2max and body fat intensifies the need for effective intervention programs that prioritize maintenance of appropriate body fat and aerobic fitness levels because inadequate levels of both factors result in negative health consequences.